1504. Risk of Influenza-Associated Hospitalization Among Older Adults Living with Diabetes — United States, 2012–2017. (31st December 2020) - Owusu, Daniel; Rolfes, Melissa A; Velezmoro, Carmen S Arriola; Reed, Carrie; Kirley, Pam Daily; Alden, Nisha B; Anderson, Evan J; Monroe, Maya; Kim, Sue; Lynfield, Ruth; McMullen, Chelsea L; Spina, Nancy; et al.
Abstract: Background: Older adults account for tens to hundreds of thousands of influenza-associated hospitalizations annually. Diabetes mellitus (DM) is common among patients hospitalized with influenza, yet data are limited on the impact of DM on influenza-associated hospitalizations. We compared influenza-associated hospitalization rates among older adults living with and without DM Methods: We included adults ≥65 years hospitalized with influenza during 2012–13 through 2016–17 from the Influenza Hospitalization Surveillance Network (FluSurv-Net), a population-based surveillance system for laboratory-confirmed influenza-associated hospitalizations conducted in defined catchment areas within 13 states. Influenza testing is clinician-directed, and surveillance officers identify cases through infection control logs, laboratory records and other disease reporting systems. Data on underlying conditions, including DM, were abstracted from medical records Population denominators were calculated using county-specific estimates of DM prevalence from the Centers for Medicare and Medicaid Services. We calculated hospitalization rates by state and season, and present pooled rates and rate ratios, with 95% confidence intervals (CI), using meta-analysis with state as a random effect. Results: Of 31, 934 patients included in the analysis, 34% had DM. DM prevalence in the FluSurv-Net source population aged ≥65 years was 25%. Accounting for variability by state, the average influenza-associated hospitalization rate per 100, 000 person years from 2012-13 through 2016-17 was 276 (95% CI: 230–330/100, 000) in those with DM and 181 (95% CI:150–217/100, 000) in those without DM. Though the magnitude of the association varied by season, hospitalization rates among those with DM was consistently greater than those without DM (pooled rate ratio: 1.57; 95% CI: 1.43–1.72; P< .0001). Conclusion: Older adults have high influenza-associated hospitalization rates, and those with DM have a 57% increased risk compared to those without DM. These findings reinforce the importance of annual influenza vaccination in adults ≥65 years of age, particularly those with DM. Disclosures: Nisha B. Alden, MPH, CDC (Grant/Research Support) Evan J. Anderson, MD, Sanofi Pasteur (Scientific Research Study Investigator) Sue Kim, MPH, Council of State and Territorial Epidemiologists (CSTE) (Grant/Research Support)